2021
DOI: 10.3390/polym13121972
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Adhesive Properties of Soy Protein Wood Adhesives with Different Coadjutant Polymers, Nanocellulose and Lignin

Abstract: Commercial wood adhesives are based on products that contain formaldehyde; however, environmental and health concerns about formaldehyde emissions from wood products have influenced research and development efforts in order to find alternative, formaldehyde-free products for wood adhesives. In this work, different soy protein-based wood adhesives are proposed, and their performance is compared to commercial urea formaldehyde (UF) adhesive. Soy protein-based wood adhesives were prepared using either soy protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“… 31 Protein adsorption on solid surfaces is driven by different types of nonspecific interactions such as hydrophobic forces, electrostatics, and hydrogen bonding 32,33 . Therefore, lignin has been utilized as a water resistance improvement for protein‐based adhesives 34–37 . The wet adhesion strength improved approximately 50% with unmodified lignin in our previous study 38 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“… 31 Protein adsorption on solid surfaces is driven by different types of nonspecific interactions such as hydrophobic forces, electrostatics, and hydrogen bonding 32,33 . Therefore, lignin has been utilized as a water resistance improvement for protein‐based adhesives 34–37 . The wet adhesion strength improved approximately 50% with unmodified lignin in our previous study 38 .…”
Section: Introductionmentioning
confidence: 81%
“…32,33 Therefore, lignin has been utilized as a water resistance improvement for protein-based adhesives. [34][35][36][37] The wet adhesion strength improved approximately 50% with unmodified lignin in our previous study. 38 Further water resistance improvement was achieved by using modified lignin.…”
mentioning
confidence: 99%
“…The G' and G" declined at the temperature of 75 °C ~ 80 °C. Podlena et al [25] found that the thermal analysis transition temperature of unmodi ed SPI was 73.8 °C. Therefore, it could be preliminarily speculated that the rheological properties of FER may be caused by the denaturation of SPI.…”
Section: Rheological Properties Of Fermentioning
confidence: 99%
“…However, the formaldehyde emission has caused environmental and health concerns because of its possibility of causing cancer. 3 Recently, soy protein adhesive was revived because the adhesive system did not contain any formaldehyde. Thus, how to overcome the disadvantages such as relatively low bonding strength and poor water resistance has become the focus of research in soy-based adhesive systems.…”
Section: Introductionmentioning
confidence: 99%